2017
DOI: 10.1183/13993003.00085-2017
|View full text |Cite
|
Sign up to set email alerts
|

Rare respiratory diseases are ready for primetime: from Rare Disease Day to the European Reference Networks

Abstract: International audience

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
(48 reference statements)
1
21
0
1
Order By: Relevance
“…This unmet need was shared by the authors of the statement, and one of the conclusions was that "The systematic collection of data concerning clinical characteristics and natural history of patients with AATD in national and international registries will enhance knowledge about the evolution of this disease and its optimal management" [3]. Therefore, the EARCO registry is the response to this unmet need; it will work in close collaboration with the European Reference Network (ERN) for respiratory diseases (ERN-LUNG) [12], the ERN for hepatological diseases (ERN RARE-LIVER) and the registry of the Alpha-1 Liver Group. In doing this, it will consider the recommendations of the European Medicines Agency about the methodology for the development of registries for regulatory purposes [13].…”
Section: Aims Of Earco: the International Registrymentioning
confidence: 99%
“…This unmet need was shared by the authors of the statement, and one of the conclusions was that "The systematic collection of data concerning clinical characteristics and natural history of patients with AATD in national and international registries will enhance knowledge about the evolution of this disease and its optimal management" [3]. Therefore, the EARCO registry is the response to this unmet need; it will work in close collaboration with the European Reference Network (ERN) for respiratory diseases (ERN-LUNG) [12], the ERN for hepatological diseases (ERN RARE-LIVER) and the registry of the Alpha-1 Liver Group. In doing this, it will consider the recommendations of the European Medicines Agency about the methodology for the development of registries for regulatory purposes [13].…”
Section: Aims Of Earco: the International Registrymentioning
confidence: 99%
“…Im Jahr 2016 hat das European Commission's Board of Member States 23 europäische Referenzgruppen (ERNs) einschließ-lich dem ERN-LUNG zugelassen [3,4]. Ziel dieser Initiative ist es, das Wissen über seltene Erkrankungen zu bündeln, Zentren zu scha en, die besondere Erfahrungen mit seltenen Lungenerkrankungen haben, Patienten zu registrieren und Empfehlungen zu verfassen.…”
Section: Seltene Erkrankungen Mit Lungenbeteiligungunclassified
“…In the UK, for example, four PCD management services have been commissioned since 2013 [89]. Expert multidisciplinary reference centres working together through international networks are starting to optimise diagnostic and clinical management [31]. The optimal number of centres per country is not known, but estimates suggest that, in a region of 10 million people, there should be 10-12 new PCD cases every year [26].…”
Section: Management Strategiesmentioning
confidence: 99%
“…Research in PCD has shown that centres managing over 20 patients are associated with diagnosis at an earlier age [17]. It is anticipated that centralised care will provide access for patients to expert centres using standardised protocols with quality assurance, such as the European Reference Network ERN-LUNG (http://ern-lung.eu) [31] and the North American Genetic Disorders of Mucociliary Clearance Consortium.…”
Section: Introductionmentioning
confidence: 99%